A comparison analysis of different photogrammetric softcopies for geodata production - Voitechovič, Mažena; Ruzgienė, Birutė (Geodesy and Cartography, 2014)
Up-to-date mapping technologies for geodata production are widely applicable in Remote Sensing and Photogrammetry Communities. Therefore, the education in Remote Sensing and photogrammetric methods becomes very important using different image processing software for the terrain mapping purposes, spatial data modelling, etc. The use of new methods, technologies and professional widely-known systems demonstrates the desire to increase mapping capability. Despite that, digital didactics photogrammetric systems might be used (particularly in education process) simultaneously, this way getting more efficiency results. The objective of the research is to analyse some aspects of the use of digital photogrammetric softcopies, applied for terrain mapping: professional IMAGE ERDAS with LPS, LISA and Didactics Digital Photogrammetric Systems (DDPS). The experimental investigations lead to contiguity of this different software in consideration of the following criteria: accuracy, flexibility and time. The digital terrain models and orthophoto maps, created using two technologies, are almost the same due to time required for separate image processing steps. However, full workflow on DDPS requires about 2.5 times less time than on LPS. The photogrammetric measurement results demonstrate that there are some differences in accuracy due to stereoscopic measurements. When processing the images, the defined value of accuracy estimators meets the requirements for topographic mapping; however, DEM needs a separate study.